Horseshoe Kidney with Bilateral Duplex Ureters - Ashok K R; Rohini K R; Kiran T V (Academia Anatomica International, 2019)
Horseshoe kidney is the most common fusion anomaly of the kidney. Its association with duplex collecting system is a rare entity. Incidence of infections, calculi and nephroblastoma increases in horseshoe kidney. Knowledge of these rare anomalies is imperative for proper diagnosis and treatment. We observed horseshoe kidney with bilateral duplex ureters in a 65-year-old male cadaver. Details of the anomaly, its embryological basis and significance are discussed in the article.